Enzymatic and chromatographic resolution procedures applied to the synthesis of the phosphoproline enantiomers. Issue 24 (31st December 2015) - Arizpe, Alicia; Rodríguez-Mata, María; Sayago, Francisco J.; Pueyo, María J.; Gotor, Vicente; Jiménez, Ana I.; Gotor-Fernández, Vicente; Cativiela, Carlos
Graphical abstract: Abstract: The preparation of enantiomerically pure pyrrolidine-2-phosphonic acid (phosphoproline, Pro P ) has been addressed through the synthesis of suitable racemates and subsequent resolution by independent enzyme-catalyzed and chiral HPLC methods. First, racemic phosphoproline derivatives bearing the necessary protecting groups have been synthesized in excellent global yields starting from inexpensive materials. Preparative HPLC resolution of the N -Cbz-protected aminophosphonate on a cellulose-based column allowed the isolation of enantiomerically pure enantiomers on a gram scale. Enzyme-catalyzed alkoxycarbonylation of the aminophosphonate was studied using different lipases, solvents, and carbonates. Candida antarctica lipase type A (CAL-A) provided the highest enantioselectivity when combined with benzyl 3-methoxyphenyl carbonate. Abstract : ( R )-(−)-Dimethyl N -(benzyloxycarbonyl)pyrrolidine-2-phosphonate: C14 H20 NO5 P >99.5% ee [ α ]D 22 = −60.0 ( c 0.53, CHCl3 ) Source of chirality: preparative HPLC resolution Absolute configuration: ( R ) Abstract : ( R )-(−)-Pyrrolidine-2-phosphonic acid: C4 H10 NO3 P >99.5% ee [ α ]D 21 = −49.8 ( c 1.1, 1 M NaOH) Source of chirality: preparative HPLC resolution Absolute configuration: ( R ) Abstract : ( S )-(+)-Dimethyl N -tosylpyrrolidine-2-phosphonate: C13 H20 NO5 PS 94% ee [ α ]D 20 = +76.7 ( c 1.0, CHCl3 ) Source of chirality: enzymatic kinetic resolution Absolute configuration: ( S )